Factors associated with common mental disorders in a hospital cleaning staff - Alves Rocha, Marcia Regina [UNESP]; Sanches Marin, Maria Jose; Seda, Juana Macias (Univ Federal Ceara, Dept Enfermagem, 2019)
Objective: to analyze the prevalence and factors associated with common mental disorders in a hospital cleaning staff. Methods: cross-sectional research with 78 cleaners. To identify the common mental disorders, data were collected through a questionnaire with sociodemographic variables and health and work conditions, from the Self Reporting Questionnaire-20. For the analysis, the chi-square test and the Pearson or Spearmann correlation were performed. Results: most participants were female, between 36 and 50 years, brown or black, and lived with a partner. There was a mental disorder prevalence of 25.6% and an association with hearing problems, dizziness, low back pain, negative health perception, and work satisfaction. The depressive mood stood out among the dimensions of the Self Reporting Questionnaire-20. Conclusion: the factors associated with the common mental disorder were: hearing problems, dizziness, low back pain, negative health perception, and work satisfaction.
Keywords: Mental Disorders; Housekeeping; Hospital; Mental Health; Occupational Health